All-optical quantization scheme by slicing the supercontinuum in a chalcogenide horizontal slot waveguide. (August 2015) - Kang, Shuai; Yuan, Jinhui; Kang, Zhe; Zhang, Xianting; Kang, Xue; Guo, Zheng; Li, Feng; Yan, Binbin; Wang, Kuiru; Sang, Xinzhu; Yu, Chongxiu
Abstract In this paper, we propose an integratable spectral quantization scheme for all-optical analog-to-digital conversion (AOADC) by slicing the supercontinuum, which is generated in a chalcogenide (As2S3) horizontal slot waveguide. The numerical simulation results show that a 4-bit quantization resolution is successfully achieved along with a signal-to-noise ratio of 23.96 dB and an effective number of bit (ENOB) of 3.98 bit. The required As2S3 waveguide length and input peak power are only 1.5 cm and 900 mW, respectively, owing to the high nonlinear coefficient of 115.8 W−1/m. It is believed that this proposed scheme can find important applications in the photonic integratable AOADC with low power consumption.